2017
DOI: 10.11646/zootaxa.4362.3.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the Cyrtodactylus irregularis complex (Squamata: Gekkonidae) from Gia Lai Province, Central Highlands of Vietnam

Abstract: We describe a new species of the genus Cyrtodactylus from Gia Lai Province, Central Highlands of Vietnam based on morphological and molecular differences. Cyrtodactylus gialaiensis sp. nov. is differentiated from other congeners by a unique combination of the following characters: Size small, maximum known SVL reaching 62.8 mm; dorsal pattern consisting of six or seven dark transverse bands between limb insertions; intersupranasals two or three; dorsal tubercles at midbody in 16-21 irregular rows, strongly dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The nuclear tree also recovered several species as paraphyletic or polyphyletic that were recovered as monophyletic in previous, more taxonomically narrower analyses (Fig. 4): Cyrtodactylus tripuraensis (Agarwal et al 2014); С. pulchellus (Grismer et al 2012a(Grismer et al , 2014aQuah et al 2019;Wood et al 2020a); С. tuberculatus (Tallowin et al 2018); С. albofasciatus, С. deccanensis, and С. speciosus (Agarwal and Karanth 2015); С. pseudoquadrivirgatus (Luu et al 2017); С. pubisulcus (Davis et al 2019(Davis et al , 2020, and С. malayanus (Davis et al 2020). The non-monophyly of the latter species, however, may have to do with GenBank misidentifications and not mito-nuclear mismatch (Davis et al 2020).…”
Section: Nuclear Datamentioning
confidence: 65%
“…The nuclear tree also recovered several species as paraphyletic or polyphyletic that were recovered as monophyletic in previous, more taxonomically narrower analyses (Fig. 4): Cyrtodactylus tripuraensis (Agarwal et al 2014); С. pulchellus (Grismer et al 2012a(Grismer et al , 2014aQuah et al 2019;Wood et al 2020a); С. tuberculatus (Tallowin et al 2018); С. albofasciatus, С. deccanensis, and С. speciosus (Agarwal and Karanth 2015); С. pseudoquadrivirgatus (Luu et al 2017); С. pubisulcus (Davis et al 2019(Davis et al , 2020, and С. malayanus (Davis et al 2020). The non-monophyly of the latter species, however, may have to do with GenBank misidentifications and not mito-nuclear mismatch (Davis et al 2020).…”
Section: Nuclear Datamentioning
confidence: 65%
“…Once believed to be a widespread, variable species, Cyrtodactylus irregularis was shown to be composed of at least 13 distinct species with very restricted geographical distributions. So far 40 Cyrtodactylus species have been recorded from Vietnam (Grismer et al 2015, Nguyen et al 2015, Le et al 2016, Luu et al 2017; the presently described species is thus the 41 th . More than 40% of the described Cyrtodactylus species recorded from Vietnam thus belong to the C. irregularis group.…”
Section: Discussionmentioning
confidence: 99%
“…irregularis Smith, 1921 was described from an open pine forest at Camly in the Langbian Plateau, Vietnam. Nazarov et al (2008) showed that it belonged to a species complex, and described C. ziegleri Nazarov, Orlov, Nguyen & Ho. The species complex has recently been the subject of numerous morphological and molecular analyses, and so far 17 species have been described, along with several additional populations whose taxonomic status is still unresolved (Nazarov et al 2008(Nazarov et al , 2012Nguyen et al 2013Nguyen et al , 2014Nguyen et al , 2017Schneider et al 2014;Luu et al 2017). The complex currently includes the following taxa: C. bidoupimontis Nazarov, Poyarkov, Orlov, Phung, Nguyen, Hoang & Ziegler, 2012, C. bugiamapensis Nazarov, Poyarkov, Orlov, Phung, Nguyen, Hoang & Ziegler, 2012, C. caovansungi Orlov, Nguyen, Nazarov, Ananjeva & Nguyen, 2007, C. cattienensis Geissler, Nazarov, Orlov, Böhme, Phung, Nguyen & Ziegler, 2009, C. cryptus Heidrich, Rösler, Vu, Böhme & Ziegler, 2007, C. cucdongensis Schneider, Phung, Le, Nguyen & Ziegler, 2014, C. dati Ngo, 2013, C. gialaiensis Luu, Dung, Nguyen, Le & Ziegler, 2017, C. huynhi Ngo & Bauer, 2008, C. irregularis, C. kingsadai Ziegler, Phung, Le & Nguyen, 2013, C. phuocbinhensis Nguyen, Le, Tran, Orlov, Lathrop, MacCulloch, Le, Jin, Nguyen, Nguyen, Hoang, Che, Murphy & Zhang, 2013, C. pseudoquadrivirgatus Rösler, Vu, Nguyen, Ngo & Ziegler, 2008, C. takouensis Ngo & Bauer, 2008, C. taynguyenensis Nguyen, Le, Tran, Orlov, Lathrop, MacCulloch, Le, Jin, Nguyen, Nguyen, Hoang, Che, Murphy & Zhang, 2013, C. yangbayensis Ngo & Chan, 2010and C. ziegleri Nazarov, Orlov, Nguyen & Ho, 2008 In their review, Nazarov et al (2012), based on morphological and mtDNA analyses, noted two unidentified populations of the Cyrtodactylus irregularis complex from southern Vietnam: (1) the Nui Chua National Park (below Nui Chua N.P.)…”
Section: Introductionmentioning
confidence: 99%
“…These include 18 named species from Vietnam recognized by Pauwels et al (2018), as well as C. buchardi David, Teynie & Ohler, 2004 from southern Laos, a species that has been hypothesized to be a member of this complex (Ngo and Chan 2010;Nguyen et al 2013Nguyen et al , 2017 but that remains phylogenetically untested owing to lack of molecular data. The monophyly of the C. irregularis group has been demonstrated by phylogenetic analysis of the COI gene from most of the species in the complex (Nazarov et al 2012;Nguyen et al 2013Nguyen et al , 2014Nguyen et al , 2017Luu et al 2017;Schneider et al 2014).…”
Section: Introductionmentioning
confidence: 99%